Red Scare:FBI and the Origins of Anticommunism in the United States - Regin Schmidt (Museum Tusculanum Press, 2004)
The anticommunist crusade of the Federal Bureau of Investigation and its legendary director J. Edgar Hoover during the McCarthy era and the Cold War has attracted much attention from historians during the last decades, but little has been known about the Bureau's political activities during its formative years. This work breaks new ground by tracing the roots of the FBI's political surveillance to the involvement of the Bureau's predecessor, the Bureau of Investigation (BI), in the nation's first period of communist-hunting, the "Red Scare" after World War I. The book is based on the first systematic and comprehensive use of the early BI files from 1908 to 1922, which have only survived on difficult-to-read microfilms deposited in the National Archives, as well as numerous collections of personal papers. The FBI's political surveillance was not a result of popular hysteria, such as scholars used to claim, or a rational response to communist spying and the Cold War confrontation, such as a number of historians have recently argued. Instead, it was an integrated part of the attempt by the modern federal state, rooted in the Progressive Era, to regulate and control any organized opposition to the political, economic and social order, such as organized labor, radical movements and African-American protest. The detailed reconstruction of the BI's role in the Red Scare during 1919 and 1920 shows that the federal intelligence officials played a crucial role in initiating the anticommunist hysteria in the United States. Despite its small staff, the BI was able to influence national events by exchanging information with a network of patriotic groups, assisting local authorities in drafting antiradical legislation and prosecuting radicals, and using congressional committees to spread its message. The Bureau also strove to discredit the strike wave and race riots of 1919 as the work of communists. The account also throws new light on such dramatic and controversial events as the Seattle General Strike, the Centralia Massacre, and the deportation of the famous anarchists Emma Goldman and Alexander Berkman. The book shows how entrenched political surveillance had become by the early 1920's and how it continued until World War II and the Cold War. Regin Schmidt, PhD, is a research fellow in the Department of History at the University of Copenhagen. Selected for the Choice Outstanding Academic Books 2002.